2014
DOI: 10.1007/s00464-014-3510-1
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive user interfaces increase efficiency in endoscope tip control

Abstract: This work shows that intuitive user interfaces can improve the efficiency of endoscope tip steering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 17 publications
(24 reference statements)
1
25
0
Order By: Relevance
“…FE are complex, expensive, and non-intuitive medical devices that are cable actuated [3]. Most of the commercially available FEs are non-disposable and require reprocessing to avoid cross-contamination [4].…”
Section: Introductionmentioning
confidence: 99%
“…FE are complex, expensive, and non-intuitive medical devices that are cable actuated [3]. Most of the commercially available FEs are non-disposable and require reprocessing to avoid cross-contamination [4].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies by Ruiter et al [1] and Rozeboom et al [67] showed that bimanual joystick interfaces allow endoscopic tip positioning with reduced workload and reduced tip trajectory. A single-handed controller is expected to further reduce the experienced workload, since it creates the illusion that the endoscope is an elongation of the right arm.…”
Section: Discussionmentioning
confidence: 99%
“…The system consists of a remote controller with which the user controls a motor drive unit and valves for air inflation, water injection and suction, Figure 6.1 [67]. Two motors in the drive unit manipulate bending cables that run through a flexible transmission to a mobile drive unit.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations